Performance of alkaline pretreatment on pathogens inactivation and sludge solubilization - Fubin, Yin; Zifu, Li; Saino, Mayiani; Hongmin, Dong (International Journal of Agricultural and Biological Engineering, 2017)
Inactivation of pathogen indicators (i.e., faecal coliforms, Salmonella spp., faecal streptococcus, and helminth eggs) were investigated during alkaline pretreatment (pH=10 and 12) in this study. The performance of alkaline pretreatment on the inactivation pathogens, kinetic of pathogens inactivation and sludge solubilization was evaluated. Results of alkaline pretreatment showed that the complete inactivation periods of pathogens time were 1.5 d, 1.5 d, 2 d, 2.5 d, 3 d, 3 d and 3 d for faecal sludge total solids (TS) of 1%, 2%, 4%, 6%, 8%, 10% and 12%, respectively. The kinetics of pathogen inactivation can be predicted better by Weibull than the first-order model. Meanwhile, the relationship between alkaline pretreatment time and the TS content of the sludge agrees with the exponential equation (y =1.3543e10.002x, 1% ≤ x ≤ 8%) and logarithmic equation (y =3, 8% ≤ x ≤ 12%). Furthermore, alkaline pretreatment can improve sludge solubilization and has a more significant effect on protein solubilization than on soluble chemical oxygen demand (SCOD).Keywords: faecal sludge, alkaline pretreatment, pathogen inactivation, kinetic, sludge solubilizationDOI: 10.3965/j.ijabe.20171002.2600Citation: Yin F B, Li Z F, Mayiani S, Dong H M. Performance of alkaline pretreatment on pathogens inactivation and sludge solubilization. Int J Agric & Biol Eng, 2017; 10(2): 216–223.